Effects of water-nitrogen interaction on photosynthetic-stoichiometric balance in potato: a leaf physiological and ecological perspective - Du, Bin; Yin, Juan; Yang, Yingpan; Li, Jinze; Tang, Ying (Frontiers in Plant Science, 2025)
Potato, a globally important food crop, plays a key role in ensuring food security and poverty alleviation. Addressing the prominent contradiction between water scarcity and low nitrogen use efficiency in potato production in the arid regions of northwest China, this study conducted a water-nitrogen regulation experiment to explore the synergistic effects of water-nitrogen management on potato yield and physiological ecology. Irrigation treatments included the full irrigation quota (2250 m3 ha-1, W3), 20% water-saving (1800 m3 ha-1, W2), and 40% water-saving (1350 m3 ha-1, W1), while nitrogen application treatments consisted of the full nitrogen rate (195 kg ha-1, N3), 20% nitrogen reduction (156 kg ha-1, N2), 40% nitrogen reduction (117 kg ha-1, N1), with the local conventional practice as the control (CK). The results showed that the W2N2 treatment had the highest chlorophyll content, which was significantly higher than other treatments and 2.87% higher than CK on average. Under water-nitrogen interaction, potato leaf gas exchange parameters first increased and then decreased with growth stages, peaking at the tuber formation stage, and the W2N2 treatment was significantly superior to other combinations. For nutrient contents in various plant organs, the W2N2 treatment also achieved the highest total nitrogen and total phosphorus contents, which were significantly higher than other treatments. The distribution ratios of nutrient contents in different organs varied with water-nitrogen treatments across years. Based on quadratic regression analysis and the TOPSIS model, the optimal water-nitrogen coupling pattern for potato cultivation in the arid zone of central Ningxia was determined as W2N2, providing theoretical and technical references for efficient potato cultivation with water-saving and nitrogen-reducing practices in arid regions.